1994
DOI: 10.1161/01.cir.89.6.2645
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-specific effects of adenosine on atrial tachycardia.

Abstract: BACKGROUND Recent reports suggest that adenosine, in addition to terminating supraventricular tachycardia involving the atrioventricular (AV) node, may have antiarrhythmic effects on atrial tachycardia. The electrophysiological effects of adenosine on supraventricular tissue include shortening of action potential duration in atrial myocytes mediated by the potassium current, IKACh,Ado; shortening of action potential duration and hyperpolarization in sinus node cells; and anti-adrenergic electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…Focal AT consistent with enhanced automaticity had the following characteristics 3 : spontaneous initiation or termination, failure to initiate with programmed stimulation, and demonstration of warm-up and cool-down phenomena. In contrast, focal AT consistent with triggered activity demonstrated reproducible initiation and termination with programmed stimulation, as well as sensitivity to adenosine and verapamil (when administered).…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Focal AT consistent with enhanced automaticity had the following characteristics 3 : spontaneous initiation or termination, failure to initiate with programmed stimulation, and demonstration of warm-up and cool-down phenomena. In contrast, focal AT consistent with triggered activity demonstrated reproducible initiation and termination with programmed stimulation, as well as sensitivity to adenosine and verapamil (when administered).…”
Section: Definitionsmentioning
confidence: 99%
“…We have previously demonstrated that atrial flutter is insensitive to adenosine. 3 Like atrial flutter, incisional ATs do not terminate with adenosine. The exception to this rule is the rare form of macroreentrant AT involving tissue with decremental conduction properties.…”
Section: Macroreentrant Atrial Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation
“…The drug terminates the vast majority of AV node dependent tachycardias producing AV block that will reveal intratrial arrhythmias. DiMarco et al demonstrated high specificity and sensitivity as well as safety of adenosine in the diagnosis of patients presenting with narrow-complex tachycardia by distinguishing between atrial tachycardias and those that require the AV node [122,123].…”
Section: Class V Antiarrhythmic Medications Adenosinementioning
confidence: 99%
“…Lerman et al have previously explored these various possibilities and found that adenosine infusion helped distinguish between the various mechanisms responsible for AT in patients. 4,5 In this issue of the Journal, Dr Lerman and his colleagues present their experience with adenosine in delineating the mechanism of AT in a large series of patients. 6 Among the 59 patients, approximately one third had undergone a prior procedure for either AF or AT.…”
Section: See Article By Liu Et Almentioning
confidence: 99%